A flexible tysonite-type La0.95Ba0.05F2.95@PEO-based composite electrolyte for the application of advanced fluoride ion battery. (October 2019) - Liu, Lei; Yang, Li; Liu, Min; Wang, Xianyou; Li, Xiaolong; Shao, Dingsheng; Luo, Kaili; Luo, Zhigao; Chen, Gairong
Graphical abstract: Highlights: La0.95 Ba0.05 F2.95 @PEO inorganic-organic solid-state composite electrolyte is prepared. The ionic conductivity of LBF05@PEO reaches a maximum of 5.75 × 10 −6 S·cm −1 at 90 °C. The electrochemical stability window of LBF05@PEO is 4.7 V versus Li/Li + at 70 °C. Fluoride ion battery FeF3 /LBF05@PEO/Li shows initial capacity of 113.5 mA h g −1 at 0.1 C. Abstract: Fluoride ion batteries (FIBs) with high theoretical energy density have been proposed as a promising competitor of lithium ion batteries (LIBs), which are based on a 'fluoride shuttle' - the reversible transfer of fluoride anions from one electrode to the other. To improve further contact between electrode and electrolyte, decrease interfacial impedance and provide buffer layer "soft interface" for volume change of electrode during charging and discharging process, here we put forward to prepare a flexible solid-state composite electrolyte based on the tysonite-type La0.95 Ba0.05 F2.95 (LBF05) inorganic particles and poly (propylene carbonate). Tysonite-type LBF05 inorganic particles are synthesized by wet chemical method, and then the solid-state composite electrolyte is prepared by reverse molding method to mix LBF05 and PEO. Morphological, chemical and structural characterizations of the solid-state composite electrolytes are studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis and differential scanning calorimetry (TGA-DSC), Fourier transfer-infrared spectrometry (FT-IR) and charge/discharge tests. It has been found that the ionic conductivity of solid-state composite electrolyte LBF05@PEO reaches a maximum of 5.75 × 10 −6 S·cm −1 at 90 °C and the electrochemical stability window reaches 4.7 V versus Li/Li + at 70 °C. Charge/discharge tests for the FIBs are conducted at 70 °C with LBF05@PEO as electrolyte, Li as anode, and FeF3 composite material as cathode. The prepared solid-state fluoride ion battery FeF3 /LBF05@PEO/Li delivers initial discharge capacity of 113.5 mA h g −1 at 0.1 C (1 C = 273 mA h g −1 ) between 1.0 V and 4.5 V. Although many works need still to be further developed, this study opens a new way to the development of solid-state composite electrolyte for advanced fluoride ion battery.